Immunotherapy as a treatment for type 1 diabetes mellitus in children and young adults: A comprehensive systematic review and meta-analysis - Gaelle Salame; Vincent Hakim; Clara Dagher; Rose-Mary Daou; Anthony El Dada; Lea Nassif; Hilda E. Ghadieh; Sami Azar; Samer Bazzi; Frederic Harb (PLoS ONE, 2025)
Background and Objective Type 1 diabetes mellitus (T1DM) is characterized by the loss of pancreatic cells, resulting in total insulin insufficiency. According to the Diabetes Control and Complications Trial, T1DM treatment aims to achieve appropriate glycemic control and to prevent and avoid repeated episodes of hypoglycemia. Insulin therapy alone addresses the symptoms of the disease but fails to target the underlying pathophysiology of T1DM in children despite continuous efforts to enhance insulin regimens. Therefore, immunotherapy-based approaches have been considered potential treatments for T1DM in children since they can regulate the autoimmune responses and enhance the children’s quality of life by reducing their daily dose intake of insulin. Methods In this meta-analysis, we have covered a few immunotherapeutic options based on preclinical and clinical data, namely, Teplizumab, Golimumab, Imatinib, Etanercept, Canakinumab, Ladarixin, Ala-Ala, Anakinra, and Otelixizumab in reliable databases such as Pubmed, Google Scholar, and Cochrane. SPSS was used for statistical analysis. Mean difference (MD) and standard mean difference (SMD) were used to evaluate the outcomes with a 95% confidence interval (CI). Results To assess the effect of immunotherapy on the patients’ daily dosage of insulin and their HbA1c and C-peptide levels, data from twelve trials were combined and synthesized. Because of the high levels of heterogeneity in the selected studies, a random-effects model was used for analysis. The combined data showed that patients receiving immunotherapy had higher C-peptide levels (Mean Difference (MD) = 1.51; 95% Confidence Interval (CI): [-2.56, 5.58]); however, this difference was not statistically significant (p = 0.42). On the other hand, patients in the immunotherapy group had significantly decreased HbA1c levels (MD = -0.63; 95% CI: [-1.18, -0.07]; p = 0.03), indicating that immunotherapy had a positive impact on glycemic management. Additionally, patients receiving immunotherapy exhibited a drop in their daily insulin dosage (MD = -1.15; 95% CI: [-2.59, 0.28]); however, this drop failed to achieve statistical significance (p = 0.10), thus indicating the need for additional research. Conclusion This meta-analysis aimed to assess the effectiveness of immunotherapy in treating T1DM by examining its effects on the patients’ required dose of insulin, C-peptide, and HbA1c levels. While some studies failed to show desired results, the overall effect was an increase in C-peptide levels and a decrease in HbA1c levels. However, the study did not achieve statistical significance for insulin dosing. The main study’s strength is its focus on randomized clinical trials which is considered among the highest levels of epidemiological evidence. Therefore, further research is required to minimize the gaps and to explore immunotherapy-based drugs as potential treatments for T1DM.